Somatotype and morphological characteristics of metabolic syndrome in patients with schizophrenia and persons without mental disorders - E. G. Kornetova; A. A. Goncharova; I. A. Mednova; A. N. Kornetov; T. V. Saprina; O. E. Perchatkina; A. V. Semke (Бюллетень сибирской медицины)
Objective: identify differences or comparability of constitutional-morphological characteristics and indicators of the fatty constitution between patients with schizophrenia and people with MetS and without mental disorders.Materials and methods. We examined 63 patients with schizophrenia and MetS (25 women, 38 men), aged 30 [33;52], and 50 mentally healthy individuals with MetS (28 women, 22 men) aged 57 [49; 60]. The main criterion for inclusion in the study was the presence of a verified MetS according to the criteria of the International Diabetes Federation. Anthropometric examination was performed according to the method of V.V. Bunak (1941) with the underlying calculation of integral indices. The determination of the fat component included: measuring waist circumference; non-invasive bioimpedancemetry – body weight, BMI, total and visceral fat content; determination of the total fat fold (electronic caliper). In the blood serum, the concentration of glucose, total cholesterol, HDL, TG was determined using standard commercial kits, the calculation of LDL and the Atherogenic Index.Results. Differences in the prevalence of the constitutional-morphological type and the type of somatic sexual differentiation were not established in the groups. The level of visceral fat and BMI were higher in mentally healthy individuals with MetS than in schizophrenic patients with MetS (p = 0.005 and p = 0.0001, respectively). Patients with schizophrenia and MetS had low serum glucose levels compared with individuals without mental disorders (p = 0.0001). An increase in the level of TG and the Atherogenic Index was found in patients with schizophrenia with MetS (p = 0.026 and p = 0.03, respectively), and the level of HDL was reduced (p = 0.022).Conclusion. The constitutional and morphological basis of MetS in patients with schizophrenia and persons without mental disorders is the same, however, changes in the fat constitution were determined for mentally healthy individuals. Changes in the lipid profile and glucose concentration may be associated with the presence of MetS-specific risk factors for patients with schizophrenia.